The Modified Alberta Reconstructive Technique: A prospective cohort study. (April 2022) - Pyne, Justin M.; Kelly, Brendan C.; Logan, Heather; Osswald, Martin; Nayar, Suresh; Biron, Vincent L.; Ansari, Kal; Harris, Jeffrey R.; O'Connell, Daniel A.; Seikaly, Hadi
Highlights: The Modified Alberta Reconstructive Technique is an advanced and effective method for jaw reconstruction. Aesthetically pleasing results can be obtained with an experienced team. Utilization of a skin graft promotes neo-gingiva which is the most similar to native gingiva. Abstract: Introduction: Jaw defect reconstructions have been transformed by the development of free tissue transfer using vascularized bone incorporating osseointegrated dental implants. We recently developed a modification our method this procedure and termed it the Modified Alberta Reconstruction Technique (MART). The objective of this study aimed to assess the soft tissue component and outcomes of the MART as compared to the Alberta Reconstructive Technique (ART) or conventional (BDD) reconstructions. Patients and Methods: This was a prospective cohort study of adult patients who underwent jaw reconstruction with dental implant rehabilitation between 2000 and 2019 in Edmonton, Alberta. Patients were aged-matched and placed into a cohort based on the type of reconstruction they received. Outcomes were compared between the groups. Expert and aesthetic analyses were performed. Statistical analysis was conducted to determine significance. Results: A total of 46 patients (15 BDD, 15 ART and 16 MART) were included. Demographics were similar between groups. There was no difference in complications. The soft tissue component of the MART cohort was more favourable to work with as judged by the occlusal reconstructive experts. The MART was rated as more aesthetically appealing in comparison to the BDD and ART (p = 0.049). Conclusions: The MART is a safe, effective, and aesthetically appealing procedure. It yields a good functional result and a clinically better soft tissue component for occlusal reconstructions. For a select group of patients requiring jaw reconstruction, the MART is an ideal reconstructive option as the modification provides good control of the soft tissue around the implants.